2013
DOI: 10.4103/0972-5229.117054
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis induced immunosuppression: Implications for secondary infections and complications

Abstract: Sepsis is the commonest cause of admission to medical ICUs across the world. Mortality from sepsis continues to be high. Besides shock and multi-organ dysfunction occurring following the intense inflammatory reaction to sepsis, complications arising from sepsis-related immunoparalysis contribute to the morbidity and mortality from sepsis. This review explores the basis for sepsis related immune dysfunction and discusses its clinical implications for the treating intensivist. Recent trends indicate that a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…In brief, the role of peptic ulcer disease with hemorrhage might be more prominent in patients recovering from advanced AKI. Although AKI involves some degree of inflammation (31)(32)(33), an "immunoparalysis" state, similar to that ensuing from sepsis and critical illness (34,35), may coexist and make the effects of H. pylori more pernicious. Our study showed, however, that a small portion of patients received H. pylori eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the role of peptic ulcer disease with hemorrhage might be more prominent in patients recovering from advanced AKI. Although AKI involves some degree of inflammation (31)(32)(33), an "immunoparalysis" state, similar to that ensuing from sepsis and critical illness (34,35), may coexist and make the effects of H. pylori more pernicious. Our study showed, however, that a small portion of patients received H. pylori eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As the most frequent cause of mortality in intensive care unit (ICU), sepsis is responsible for over 250,000 deaths each year in the United States (Martin, Mannino & Moss, 2006). Numerous studies have shown that the predominant driving force for morbidity and mortality of sepsis is immunosuppression (Hotchkiss, Monneret & Payen, 2013a; Hotchkiss & Nicholson, 2006; Hotchkiss & Opal, 2010; Hotchkiss et al, 2005; Sundar & Sires, 2013). Apoptosis of various immune cells has been proposed as a critical mediator of this sepsis-induced immunosuppression (Hotchkiss, Monneret & Payen, 2013b; Hotchkiss & Nicholson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis can be potentially life threatening; of more than 1 million Americans who are diagnosed with severe sepsis every year, between 28 and 50% will die from this disease (1,2). It is well-recognized that patients with sepsis are often immune suppressed, a state of reduced responsiveness to endotoxin known as endotoxin tolerance, deaths in this immunosuppressive phase are typically due to failure to control the secondary infections (3)(4)(5). The molecular mechanisms underlying this endotoxin tolerance phenomenon is poorly understood.…”
mentioning
confidence: 99%